PENGARUH KEDISIPLINAN, ETOS KERJA DAN KETERAMPILAN KERJA TERHADAP KINERJA KARYAWAN PADA PT PURI PANGAN SEJATI - I Wayan Dony Eka Putra; I Wayan Sujana; Ni Nyoman Ari Novarini (EMAS, 2022)
At this time the development of a company in terms of human resource development is very large, because human resources are something that is functional in achieving the company's goals optimally. Every company should understand and pay attention to the factors that can affect the increase of human resources themselves. The sample in this study was all active employees of PT Puri Pangan Sejati as many as 50 people. The sample determination technique used is the Purposive sampling method. The data collection techniques used in the study were observations, interviews and questionnaires. Data analysis techniques include validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation anlysis, determination analysis (R2), f test and t test. The results showed that Discipline, Work Ethic and Work Skills have a positive and significant effect on employee performance, so leaders should make specific rules about behavior that is accepted and not in the company, motivate employees to work hard, provide rewards and job training and change employee mindset, so as to improve employee performance at PT. Puri Pangan Sejati.